Phakopsora pachyrhizi survival in volunteer soy plants in Planalto Norte and Planalto Serrano regions of Sc, Brazil - Gallotti, Gilson José Marcinichen (2020)
In this study we report the evaluaton of the occurrence of volunteer plants of soybean with or without the incidence of rust in the regions Planalto Norte and Planalto Serrano in Santa Catarina state, southern Brazil, between June 15th and September 15th, 2009. We evaluated 67 crops: 56 in Planalto Norte and 11 in Planalto Serrano. The plants were sent to the Laboratory of Plant Pathology at Epagri/Experiment Staton of Canoinhas, in Canoinhas, and to Udesc, in Lages, both in SC, where the presence of rust was examined under stereoscopic microscope. There was occurrence of volunteer plants and theabsence of soybean rust in these plants.